Działalność patentowa Polski na tle świata - Piekut, Marlena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of the article was to present the position of Poland in the competition rankings, with a special focus on the number of patents submitted to the European Patent Office and the United States Patent and Trademark Office. The conducted analysis points at Poland’s distant position, among European countries, in rankings of competitiveness, in terms of inventive and patent activity. It is necessary to encourage Polish entrepreneurs to finance research and developments activities, as well as to use the latest scientific achievements. European Funds can be helpful in financing the above mentioned measures.